ANALYSIS OF POTENTIAL LAND FOR RELOCATION RESIDENTIAL AREA IN SIMALUNGUN REGENCY - Suhenpi Laia; Ihsan Azhari; Cut Nuraini (Bulletin of Engineering Science, Technology and Industry, 2024)
Spatial planning is a structured planning from various considerations of analysis and projection results so as to produce concrete planning to be used as a reference in effective, efficient and sustainable spatial utilization. Emergency or urgent conditions such as disasters, conflicts, strategic projection development and so on that require an existing residential area to be relocated, then the handling has the potential to be inconsistent with spatial planning. Placement of relocation areas is often directed at land with the status "Available" without having to ensure its status "In accordance" with the spatial plan. This study was conducted to find land that is available and in accordance with the spatial plan as a potential area for relocation of residential areas. This study is a quantitative study with the superimpose analysis method, namely carrying out a spatial overlap process on the variables (Disaster Prone, Land Capability Unit, Spatial Pattern Plan, Existing Land Cover and Land Legality Status) that have been determined. From the results of the research that has been carried out, there is land that is suitable to be used as a relocation area112,161.6 hectares. However, based on the availability of land ownership legality data, Simalungun Regency has 6 locations to be used as alternatives for relocation of residential areas with a total area of 20.68 hectares. For greater needs in the future, land with an area of 112,161.6 hectares can be used as an alternative.